Hydrogen bonding-mediated phase-transition gelatin-based bioadhesives to regulate immune microenvironment for diabetic wound healing - Zhuoling Tian; Ruoheng Gu; Wenyue Xie; Xing Su; Zuoying Yuan; Zhuo Wan; Hao Wang; Yaqian Liu; Yuting Feng; Xiaozhi Liu; Jianyong Huang (Bioactive Materials)
Gelatin-based biomaterials have emerged as promising candidates for bioadhesives due to their biodegradability and biocompatibility. However, they often face limitations due to the uncontrollable phase transition of gelatin, which is dominated by hydrogen bonds between peptide chains. Here, we developed controllable phase transition gelatin-based (CPTG) bioadhesives by regulating the dynamic balance of hydrogen bonds between the peptide chains using 2-hydroxyethylurea (HU) and punicalagin (PA). These CPTG bioadhesives exhibited significant enhancements in adhesion energy and injectability even at 4 °C compared to traditional gelatin bioadhesives. The developed bioadhesives could achieve self-reinforcing interfacial adhesion upon contact with moist wound tissues. This effect was attributed to HU diffusion, which disrupted the dynamic balance of hydrogen bonds and therefore induced a localized structural densification. This process was further facilitated by the presence of pyrogallol from PA. Furthermore, the CPTG bioadhesive could modulate the immune microenvironment, offering antibacterial, antioxidant, and immune-adjustable properties, thereby accelerating diabetic wound healing, as confirmed in a diabetic wound rat model. This proposed design strategy is not only crucial for developing controllable phase-transition bioadhesives for diverse applications, but also paves the way for broadening the potential applications of gelatin-based biomaterials.